The teaching situation of the department of English in the universities of Bangladesh: a critical evaluation - Md. Ruhul Amin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
It has a long history of teaching English literature and language in this sub-continent. The European colonial rulers introduced this teaching with the motive of serving their own purpose, but paradoxically this teaching has benefited the people of this soil as well in many ways. From the very beginning, the English department of any college or university has been treated as one of the most prestigious departments that have produced the best citizens of this soil. But recently the teaching scenario of these departments in Bangladesh is being severely affected owing to different kinds of changes that have occurred in the social and academic arenas of the country. It is now the demand of the present time that the English departments of the universities of our country should take proper steps to address those problems properly and bring back its reputation. The present study attempts to find out the problems that are affecting the teaching and learning process of these departments and thereby damaging the glory and reputation of them, and also to provide some suggestions to cope with those problems.